(untitled) (Bangladesh Journal of Medical Education, 2019)
This descriptive type of cross sectional mixed method study was conducted with four specific objectives to understand the perception, area, ways and barriers in socialization of undergraduate medical students in Bangladesh. The study was conducted in 8 (eight) medical colleges of which 6 (six) are public and 2 (two) are private. The study was conducted for one year from July 2017 to June 2018. Total 712 student of final phase participated in the study. In- depth interview was conducted with teachers. Convenience sampling technique for selection of the students whereas medical colleges were selected purposefully. Study revealed that most of the asked parameters related to patient care and humanistic attitude was taught to the undergraduate medical students of the selected medical colleges in Bangladesh. There are few concerns though in some area like number of role models and presence of negative role models among the teachers. Contents, aim and objectives of the current curriculum is vastly unknown to teachers. A conscious attempts to be made to transform medical students in a positive manner. Teachers should be selected following a proper career planning and they should undergo some kind of courses before deployment which would give them an understanding on teaching methodology and capability to foster ethically compatible as well as technically skill medical students of current era. Bangladesh Journal of Medical Education Vol.10(1) 2019: 14-19